PENGARUH MANAJEMEN LABA DAN TAX PLANNING DENGAN KONSERVATISMA AKUNTANSI SEBAGAI VARIABEL INTERVENING TERHADAP SENGKETA PAJAK PENGHASILAN - Desi Paradina; M. Irfan Tarmizi (JABE (Journal of Applied Business and Economic), 2015)
The purpose of the study is to examine the effect of earnings management and  tax planning with accounting conservatism as an intervening variable for income tax dispute. The statistical method which is used to test the hypothesis of this study is path analysis. Sampling is done by using purposive random sampling, where sample included in the study had to meet certain criteria, after the selection that based on estabilished criteria, then the final sample of 10 companies obtained. The path analysis test results are earnings management and tax planning variable influence to tax dispute, while earnings management and tax planning variable throught accounting conservatism don’t influence to tax dispute and earnings management and tax planning variable jointly affect tax dispute through conservatism accounting. All of these studies also support the theory of motivation.